The lady vanishes [videorecording (DVD)] - Lawrence, Diarmuid; Middleton, Tuppence, 1987-; Cadell, Selina; Hawes, Keeley, 1976-; White, Ethel Lina (BBC, 2014)
When a woman suddenly vanishes while traveling across Europe by train, her fellow passengers pretend she never existed.